Analysis Of Communication Media Assistance On The Program Keluarga Harapan (PKH) In The Implementation Of Family Development Session (FDS)” - Istiani, Ade Nur; Mansyur, M. (Universitas Islam Negeri Raden Intan Lampung, 2022)
The Family Hope Program (PKH) is a conditional cash transfer program given to poor families in Indonesia. PKH in the long term is expected to be able to break the chain of poverty between generations through improving the conditions of education and health in PKH families which are obtained through FDS activities. The success of FDS cannot be separated from the use of communication media in improving the quality of beneficiary families as well as recipients of messages about education, health and improving the family economy. The method used in this study is a qualitative descriptive method. Research informants were determined by purposive sampling technique . Data collection techniques are carried out by means of observation, in-depth interviews (in- depth interview) and documentation. Data analysis procedures or techniques used are data reduction , data display , and conclusion drawing. The results of this study show Communication media in the form of videos, flipcarts and smart books that are used by PKH facilitators in the Family Development Session process make it very easy for mothers to receive material from their companions, and have a good impression on mothers participating in the family of hope program in Batu Putuk Village, Teluk Betung Barat, Bandar City. Lampung. In terms of health, education and economy, they are able to shape the mothers of PKH Beneficiaries into quality families.